2012
DOI: 10.1038/mt.2011.257
|View full text |Cite
|
Sign up to set email alerts
|

RNAi Targeting CXCR4 Inhibits Tumor Growth Through Inducing Cell Cycle Arrest and Apoptosis

Abstract: CXC chemokine receptor 4 (CXCR4) is involved in many human malignant tumors and plays an important role in tumor growth and metastasis. To explore the effects of CXCR4 expression on the malignant cells of oral squamous cell carcinoma (OSCC), Tca8113 and SCC-9 cell lines, as well as their xenograft models, of nude mice were used to detect cancer cell proliferation alteration. This study also examined the corresponding molecular mechanism after CXCR4 knockdown using a recombinant lentiviral vector expressing sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 45 publications
4
20
0
Order By: Relevance
“…In this report, we showed that LY25109204 caused a significant and concentration-dependent decrease of nuclear intensity in the Namalwa xenograft model, suggesting that it may affect the G 1 to G 2 -M progression of the cell cycle. The cell cycle and proliferation effects observed in this model were consistent with other reports (3,12,30). Surprisingly, in the lymphoma Namalwa xenograft model, we have not observed significant impact on the tumor vasculature based on CD31 staining.…”
Section: Discussionsupporting
confidence: 81%
“…In this report, we showed that LY25109204 caused a significant and concentration-dependent decrease of nuclear intensity in the Namalwa xenograft model, suggesting that it may affect the G 1 to G 2 -M progression of the cell cycle. The cell cycle and proliferation effects observed in this model were consistent with other reports (3,12,30). Surprisingly, in the lymphoma Namalwa xenograft model, we have not observed significant impact on the tumor vasculature based on CD31 staining.…”
Section: Discussionsupporting
confidence: 81%
“…To extend these observations to human T-ALL, we first silenced CXCR4 in human Jurkat T-ALL cells using two distinct shRNAs (Yu et al, 2012) (Figures 6A and 6B; Figure S4A) and analyzed their in vitro and in vivo phenotypes. We found that CXCR4 silencing inhibited Jurkat cell migration and proliferation while increasing apoptosis (Figures 6C-6E; Figures S4B-S4D).…”
Section: Cxcr4 Is Required For Human T-all Leukemogenicitymentioning
confidence: 98%
“…AMD3100 significantly inhibited the lung metastasis, ameliorated body weight loss, and improved the survival rate of mice. Blocking CXCR4 via an siRNA strategy can also induce anti-tumor effects [114, 115]. Furthermore, TN14003, a small synthetic peptide antagonist of CXCR4, can reduce tumor growth, microvessel density, and lung metastasis in tumor-bearing nude mice (Table 1 ) [116].…”
Section: Cxcr4 Inhibition Against Head and Neck Malignanciesmentioning
confidence: 99%